The Syncretism of the Gabonese Bwiti Religion and Catholic Christianity from a Theological and Theological-Ethical Perspective - Ondřej Havelka (Acta Universitatis Carolinae Theologica, 2022)
The article deals with the theology and theological ethics of syncretism of the traditional Gabonese Bwiti religion and Catholic Christianity in equatorial Africa. Traditional Bwiti religious rituals are based on the consumption of the root of the iboga shrub, which has strong psychedelic effects. In Gabon, some believers profess syncretism, which is enshrined in the Bwiti initiation ritual through the Catholic Sacrament of Penance, the Holy Communion, Christian prayers, etc. These Catholic Christians thus undergo a complex and physically demanding initiation process in Gabon. The aim of the paper is to answer the basic question of the whole text, i.e. is the psychedelic initiation ritual in the depths of the Gabonese rainforest consistent with the theological and theological-ethical foundations of the Catholic Christian life? The topic is elaborated by the method of own field research, supported by a comparison of relevant literature. Between 2001 and 2019, the author spent a total of three years on research stays in Africa, of which 12 months were devoted to West and Central Africa and the study of local syncretisms.